Spatial microfluidic holographic integrated platform for label-free and high-dimensional analysis of cancer heterogeneity - Jiayi Shi; Huijing Teng; Ziyi Zhang; Yanping Liu; Dan Gao; Jianglei Di; Zijian Yang; Ping Su; Ying Tan; Jianshe Ma (Nature Communications)
Abstract The combination of quantitative phase microscopy (QPM) with imaging flow cytometry (IFC) enables label-free and multi-parameter single-cell analysis. Here, we present a simple yet powerful QPM-IFC platform, the spatial microfluidic holographic integrated (SMHI) platform, which uniquely integrates spatial hydrodynamic focusing microfluidics with digital holographic microscopy (DHM) to achieve high-fidelity single-cell QPM reconstruction without digital refocusing in 0.34 seconds, accounting for only 4.41% of the typical process ( ~ 7.71 seconds). We develop a high-dimensional phase feature hierarchy and implement a maximun-relevance and minimun-redundancy incremental feature selection (MRMR-IFS) strategy, which effectively addresses feature redundancy and constructs the optimal feature set. Consequently, a prediction accuracy of >99.9% is achieved across multiple cancer cell types, breast cancer subtypes, and blood cells, demonstrating its efficacy in analyzing highly heterogeneous cell populations. Notably, this system also exhibits high accuracy in analyzing simulated blood samples, highlighting its great potential in practical applications.